2017
DOI: 10.1002/cne.24161
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of intermingling pools of projection neurons with distinct targets: A 3D analysis of the commissural ganglia in Cancer borealis

Abstract: Cross-section through adult mouse retina showing morphology of M€ uller glial cells (green). Labeling with a membrane-targeted green fluorescent protein reveals the fine structure of M€ uller cell arbors within the inner plexiform layer (IPL) neuropil. Sublaminae S2 and S4 of the IPL are labeled with anti-choline acetyltransferase (purple). M€ uller arbor density is lowest in S2 and S4, but high in other IPL substrata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 84 publications
(170 reference statements)
2
19
0
Order By: Relevance
“…We found that network activity was reflective of spatially distributed, highly overlapping, yet distinct network responses when comparing between IV and VCN sensory modalities. This feature was consistent with almost no variability across animals, despite the rather large anatomical variability observed in this region (Follmann et al, 2017). Our results also show a relationship between CoG premotor network activation and participation and pyloric activity.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We found that network activity was reflective of spatially distributed, highly overlapping, yet distinct network responses when comparing between IV and VCN sensory modalities. This feature was consistent with almost no variability across animals, despite the rather large anatomical variability observed in this region (Follmann et al, 2017). Our results also show a relationship between CoG premotor network activation and participation and pyloric activity.…”
Section: Discussionsupporting
confidence: 90%
“…The neurites of both pathways terminated in the neuropil of the CoG ( fig. 2A, dotted area), a region associated with overlapping innervation from other sensory and modulatory pathways, as well as from ascending thoracic and descending brain fibers (Wiersma, 1957;Follmann et al, 2017). Despite morphological variation in CoG size and shape (see (Follmann et al, 2017)), IV and VCN fibers consistently overlapped within the neuropil (N=6).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations